1990
DOI: 10.1111/j.1600-0714.1990.tb00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentin dysplasia Type II: absence of Type III collagen in dentin

Abstract: A three-generation family with dentin dysplasia (DD) Type II is presented. Affected family members share common radiologic features with clinically varied expression of tooth discoloration and occlusal wear. Both the primary and the permanent dentition appear to be affected. No generalized connective tissue involvement is found. The mode of inheritance is autosomal dominant. Histologically, the findings are consistent with DD Type II. In indirect immunofluorescence, the irregular radicular dentin of an affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…In an earlier study, reticulin fibers have been found to be abundant in dentin matrix in DD type II (6), and dehcate fibers were occasionally observed in the primary tooth examined in the present study as well. However, our finding that the affected dentin contains abnormally coarse collagen fibers, is in good agreement with the negative immunostaining for type III (pro-)collagen (5). The present findings further suggest that even though the affected permanent teeth have normal coronal dentin, the structural aberrations of their radicular dentin, compared to those found in the primary teeth, are even more severe.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In an earlier study, reticulin fibers have been found to be abundant in dentin matrix in DD type II (6), and dehcate fibers were occasionally observed in the primary tooth examined in the present study as well. However, our finding that the affected dentin contains abnormally coarse collagen fibers, is in good agreement with the negative immunostaining for type III (pro-)collagen (5). The present findings further suggest that even though the affected permanent teeth have normal coronal dentin, the structural aberrations of their radicular dentin, compared to those found in the primary teeth, are even more severe.…”
Section: Discussionsupporting
confidence: 91%
“…The fibers, which were found to form large atubuIar areas, seemed to be either hazardously scattered in the loose-textured dentin matrix or they seemed to form dense, curvy bundles. The normal tubular appearance ofthe coronal dentin, and the abnormal, often atubular, structure ofthe affected radicular dentin in DD type II have been reported in a number of earlier studies (1,(3)(4)(5).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A careful examination of these cases shows that DGI-II is often present in other members of the family related to the patient or in the patient himself with also discoloration of their permanent teeth. 55 An allelic relation between these two pathologies was proposed by McDougall 38 and Dean based on linkage analysis. 56 Description of DSPP mutation in a patient affected by DD-II confirmed this hypothesis and explained these clinical similarities.…”
Section: Dentin Dysplasia Type I or Radicularmentioning
confidence: 99%
“…The permanent teeth appear normal with respect to shape, form, and color in most cases, although the pulp cavities of permanent teeth may show a thistle‐tube deformity and commonly contain pulp stones. Unlike in DD‐I, the roots are of normal length and idiopathic periapical radiolucencies are not observed . To date, fewer than 90 families/cases of DD have been reported in the literature, including two cases of DD‐II and one case of DD‐III.…”
Section: Classification Of Hereditary Dentin Disordersmentioning
confidence: 99%